2022
DOI: 10.3390/cancers14246070
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Imaging of Lung Cancer with Hyperpolarized 129Xe MRI Using Surface-Modified Iron Oxide Nanoparticles as Molecular Contrast Agents

Abstract: Hyperpolarized 129Xe (HP 129Xe) MRI enables functional imaging of various lung diseases but has been scarcely applied to lung cancer imaging. The aim of this study is to investigate the feasibility of targeted imaging of lung cancer with HP 129Xe MRI using surface-modified iron oxide nanoparticles (IONPs) as molecular targeting contrast agents. A mouse model of lung cancer (LC) was induced in nine mice by intra-peritoneal injection of urethane. Three months after the urethane administration, the mice underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The overexpression of folate receptor alpha in the majority of ovarian malignancies have led to the development of anti-folate receptor alpha SPIONs that can reliably detect ovarian tumors. 151 Lung tumors can also be visualised by taking advantage of the overexpressed folate receptor, as Kimura et al 152 showed by using polyethylene glycol-coated and dextran-coated SPIONs. Furthermore, using a hipoxia-sensitive metronidazole moiety, Yang et al 153 was able to accurately measure hipoxia in lung tumors using T 1 -weighted sequences, predicting tumor development.…”
Section: Next-generation Magnetic Nanoparticles In Mri: Translating R...mentioning
confidence: 99%
“…The overexpression of folate receptor alpha in the majority of ovarian malignancies have led to the development of anti-folate receptor alpha SPIONs that can reliably detect ovarian tumors. 151 Lung tumors can also be visualised by taking advantage of the overexpressed folate receptor, as Kimura et al 152 showed by using polyethylene glycol-coated and dextran-coated SPIONs. Furthermore, using a hipoxia-sensitive metronidazole moiety, Yang et al 153 was able to accurately measure hipoxia in lung tumors using T 1 -weighted sequences, predicting tumor development.…”
Section: Next-generation Magnetic Nanoparticles In Mri: Translating R...mentioning
confidence: 99%
“…In SEOP, circularly polarized light is exploited to optically pump rubidium (Rb) electrons and generate a highly spin-polarized Rb gas; the spin polarization is then transferred to noble gas nuclei through spin-exchange collisions. 129 Xe proved to be a suitable gas for clinical studies where it can be used for functional MRI in the lungs [24][25][26] among other applications [27,28]. Techniques such as parahydrogen-induced polarization (PHIP) and dynamic nuclear polarization (DNP) showed great promise for the production of injectable hyperpolarized contrast agents in the liquid state.…”
Section: Brief Overview Of Hyperpolarization and Dissolution-dynamic ...mentioning
confidence: 99%
“…Additionally, aptamers and peptides functionalization of NPs is used for liver cancer [37,38] visualization. The PEG coated MIONPs, and dextran (DEX)-coated IONPs conjugating folate on their surface are perspective molecular contrast agents for lungs cancer detection [39].…”
Section: Targeted Contrast Agentsmentioning
confidence: 99%